Biogeochemical research priorities for sustainable biofuel and bioenergy feedstock production in the Americas - Gollany, Hero T.; Titus, Brian D.; Scott, Andrew; Asbjornsen, Heidi; Resh, Sigrid C.; Chimner, Rodney Allen; Kaczmarek, Donald J.; Leite, Luiz F.; Ferreira, Ana C.; Rod, Kenton A.; Hilbert, Jorge Antonio; Galdos, Marcelo; et al. (2018)
Rapid expansion in biomass production for biofuels and bioenergy in the Americas is increasing demand on the ecosystem resources required to sustain soil and site productivity. We review the current state of knowledge and highlight gaps in research on biogeochemical processes and ecosystem sustainability related to biomass production. Biomass production systems incrementally remove greater quantities of organic matter, which in turn affects soil organic matter and associated carbon and nutrient storage (and hence long-term soil productivity) and off-site impacts. While these consequences have been extensively studied for some crops and sites, the ongoing and impending impacts of biomass removal require management strategies for ensuring that soil properties and functions are sustained for all combinations of crops, soils, sites, climates, and management systems, and that impacts of biomass management (including off-site impacts) are environmentally acceptable. In a changing global environment, knowledge of cumulative impacts will also become increasingly important. Long-term experiments are essential for key crops, soils, and management systems because short-term results do not necessarily reflect long-term impacts, although improved modeling capability may help to predict these impacts. Identification and validation of soil sustainability indicators for both site prescriptions and spatial applications would better inform commercial and policy decisions. In an increasingly interrelated but constrained global context, researchers should engage across inter-disciplinary, inter-agency, and international lines to better ensure the long-term soil productivity across a range of scales, from site to landscape.